A real-time hybrid correlator for synthetic aperture radar signal processing - Koo, V. C.; Chan, Y. K.; Lim, T. S. (2007)
Synthetic Aperture Radar (SAR) image formation is based on a coherent processing approach to build a long azimuth synthetic aperture. Due to the curvature and the range variance of the azimuth modulation, SAR image formation is inherently a two dimensional process. Two key elements in designing a digital SAR processor are the processing speed and memory requirements. For real-time SAR processing, the high computational requirements cannot be provided by a sequential processor system. In this paper, a new real-time SAR processor based on sub-aperture processing approach is presented. This scheme, called the Real-Time Hybrid Correlator (RTHC), achieves range correlation in frequency domain, followed by azimuth correlation in time domain. The proposed RTHC is a computationally efficient scheme without the need of corner-turn memory. Due to its distributed architecture, dedicated parallel processors can be employed for real-time processing.